Analisis Penerapan Kurikulum Merdeka Belajar Disekolah Penggerak Di Lombok Timur - Aini, Qurratul; Sholihah, Nuro; Zikriatunniza, Zikriatunniza (Universitas Hamzanwadi, 2023)
Kurikulum Merdeka Belajar (The independent Learning Curriculum) has been implemented at SMAN 1 Lenek, SMAN 1 Pringgasela, and SMAN 1 Masbagik, although this is not without the existing problems. The implementation is still being carried out in stages for SMAN 1 Lenek and SMAN 1 Pringgasela, only for tenth and eleventh grades. Meanwhile SMAN 1 Masbagik has implemented it for all classed this year, the implementation of which is not free as well from problems in terms of planning, implementation and assesment. Therefore, this researchaims to (1) To find out the implementation of the Kurikulum Merdeka Belajar in driving schools in East Lombok; (2) To find out the problems of teachers in implementing Kurikulum Merdeka Belajar in schools with penggerak concept in East Lombok; (3) To find out the efforts made bay teachers to overcom problems in imlementing the Kurikulum Merdeka Belajar in East Lombok. Methodes: qualitative research with a deskripstive type. Research subjects were the principal, deputy head of curriculum, tenth grade teachers, and tenth grade students. Results: First, at SMAN 1 Lenek, SMAN 1 Pringgasela and SMAN 1 Masbagik schools had implemented the Kurikulum Merdeka Belajar with project-based implementation, diagnostic assesments, formative assesments, and summative assesments, ATP and Teaching Modules, CP, TP. Second, teacher problems in implementing the Kurikulum Merdeka Belajar were focused in plenning, implementing and assesing learning with the difficulty of creating teaching modules, the difficulty of implementing the learning goal flow, the teachers lack of ability to use tecnology, the limited number of student textbooks, the teachers ability to allocate time during learning, teachers have difficulity giving grades to students who rarely come in. Third, the efforts made by teachers to overcome existing problems were holding meetings with the